Keefektifan Model Inquiry Training dalam Pembelajaran IPA untuk Meningkatkan Hasil Belajar Siswa SMP Negeri 1 Kota Ternate - Asri S. Tamalene; Insih Wilujeng (UNIVERSITAS KHAIRUN, 2022)
The purpose of this study was to determine the effectiveness of inquiry training models in science learning to improve the learning student learning outcomes of junior high school state one in ternate city. This type of research uses a pre-experimental design with a research design namely One Group Pretest-Posttest design. Data collection instruments used in this study were in the form of multiple choice test questions and observation sheets. The results showed that the inquiry training model was declared effective in improving the student learning outcomes in the cognitive domain with a significance value 0.005. The average attitude of students is in the category of